Effects of leadership consideration and structure on employee perceptions of justice and counterproductive work behavior. (14th September 2012) - Holtz, Brian C.; Harold, Crystal M.
Summary In this paper, we examine the effects of leadership consideration and structure on two important organizational behavior outcomes: employee perceptions of organizational justice and counterproductive work behavior (CWB). We examine these effects across two studies using multisource data (employees and supervisors in Study 1; employees and coworkers in Study 2). Results reveal that consideration and structure have distinct effects across distributive, procedural, informational, and interpersonal dimensions of justice. Moreover, results suggest that consideration and structure have multiplicative effects on employee CWB. We find the highest levels of CWB among employees of supervisors who exhibit high structure and low consideration. Interestingly, results also suggest that the effects of structure on CWB may be curvilinear (u‐shaped) such that moderate levels of structure are associated with the lowest levels of CWB. We discuss implications for future consideration and structure research as well as managerial practice. Copyright © 2012 John Wiley & Sons, Ltd.